Sustainability in the prospective scenarios methods: A case study of scenarios for biodiesel industry in Brazil, for 2030. (September 2016) - Dias, Maria Amelia de Paula; Vianna, João Nildo de Souza; Felby, Claus
Highlights: New dimensions in the scenario methods may provide sustainable images for the future. Enlarging the frameworks of the mental maps allow new perspectives of the reality. Sustainable future for biodiesel will depend on the response to climate change. Territory, social, political and environment aspects are the key for biodiesel. Abstract: In order to build prospective scenarios for biodiesel industry in Brazil, with a sustainable perspective, it was necessary to develop a cross-disciplinary work to include Sachs' dimensions of sustainability into the scenarios method. This meant linking concepts from different disciplines, without transforming it in a new discipline. In order to support the proposition for the new method, a study case is presented, the framework for the biodiesel scenarios in Brazil, by 2030. An in-depth interview was used to test the proposition of having the sustainability dimensions as driving forces. The result was the identification of a critical uncertainty composed of various aspects related the response to climate change and environmental conservation. The scenario storylines that were developed based on the critical uncertainties showed that sustainable options for the future are possible if the mental maps are enlarged to see beyond the business as usual. The results show that the scenarios storylines go through social, environmental and economic aspects, supported by other aspects like the territorial and political. Also it showed that sustainable options are possible if the mental maps are enlarged to see beyond the business as usual.